Trends in demographic, family planning, and health indicators in Ghana, 1960-2003: Trend analysis of Demographic and Health Surveys data - ORC Macro (DHS Trend Reports No. 2, 2005)
This report highlights trends in population, family planning, and maternal and child health indicators in Ghana based on DHS surveys conducted between 1988 and 2003. In particular, the report addresses the prevailing demographic situation and describes trends in fertility, family planning, maternal and child health as well as infant and child mortality. Women now wait longer to have their first birth and the proportion of young women age 15-19 that have had a child or are pregnant with their first child has declined. Current use of any modern contraceptive method has steadily increased for women age 15 to 49, along with their desire to stop childbearing. The percentage of all women between the ages of 15 and 49 who have ever used any modern contraceptive method has steadily increased between 1979 and 2003. The number of currently married women who have responded that they want no more children has increased three-fold since the 1979-1980 study. Infant and under-five child mortality rates show a marked decline. Compared from 1988 to 2003, surveys show a marked decline in both and under-five mortality in the 1988 GDHS to the 1998 GDHS three earlier surveys, but that decline levels off at during the time of surveyed in the 2003 survey.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents the findings from a trend analysis undertaken as part of the follow-up to the 2003 Ghana Demographic and Health Survey. Funding was provided by the U.S. Agency for International Development (USAID) through the MEASURE DHS project. ORC Macro provided technical assistance. The opinions expressed herein are those of the authors and do not necessarily reflect the views of USAID. The Demographic and Health Surveys program is designed to collect, analyze, and disseminate data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Additional information about the MEASURE DHS project can be obtained from ORC Macro, DHS, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705 (telephone: 301-572-0200; fax: 301-572-0999; e-mail: reports@orcmacro.com; internet: www.measuredhs.com).